Preparation process of phenolic aldehyde cotton cloth laminated board
Through the preparation process of phenolic cotton laminate, including fiber pretreatment, ultrasonic vibrator use and segmented hot pressing, the bubble defects and strength maintenance problems in the laminate in the laminate are solved, and high strength and good humidity and heat circulation performance are achieved.
Patent Information
- Application Number
- CN202510301401.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-14
- Publication Date
- 2025-04-15
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The laminate may have bubbles during the production process, affecting performance and strength, and it is difficult to maintain strength in humid and hot environments.
The preparation process of phenolic cotton laminate is adopted, including fiber pretreatment, ultrasonic vibrator use, segmented hot pressing and post-treatment steps, through which bubble defects are reduced and strength retention is improved.
It effectively reduces bubble defects, improves the strength of the laminate and the strength retention rate after humid and heat cycle, and is suitable for humid and heat environments.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of laminated boards, and in particular relates to a preparation process of a phenolic cotton cloth laminated board. Background Art
[0002] Laminate is a type of laminated product. Laminate is a whole made of two or more layers of resin-impregnated fibers or fabrics that are laminated and hot-pressed. Laminates can be processed into various insulation and structural parts and are widely used in motors, transformers, high and low voltage electrical appliances, electrical instruments and electronic equipment. Depending on the use environment, there are different requirements for the various performance parameters of laminates.
[0003] The following problems may occur during the production of laminates: first, bubbles may exist during the process of substrate dipping, which will seriously affect the performance and strength of the laminates; second, post-processing of the formed laminates, when there are pores in the laminates, it is impossible to remedy and repair them in time; in addition, some laminates need to be used in a hot and humid environment, and have a high demand for the retention rate of hot and humid strength. Summary of the invention
[0004] The present invention provides a preparation process of a phenolic cotton cloth laminate to solve at least one of the above technical problems.
[0005] The technical solution adopted by the present invention is: a preparation process of a phenolic cotton cloth laminate, comprising the following steps: S1. Fiber pretreatment: After degreasing, the cotton cloth is treated in a nitrogen plasma device for 3-8 minutes at a power of 300-500W to form a microporous structure on the surface of the cotton cloth; S2, resin synthesis: phenol and formaldehyde are mixed in a molar ratio of 1:1.0-1.3, 0.5wt%-1.5wt% oxalic acid catalyst is added, and the mixture is reacted at 85-95°C for 2-2.5 hours to obtain a thermoplastic phenolic resin; S3, dipping and defoaming: dipping the cotton cloth treated in step S1 into the thermoplastic phenolic resin obtained in step S2, setting an ultrasonic vibrator in the dipping tank, the working frequency of the ultrasonic vibrator is 25-35kHz, the power density is 80-120W / m², the dipping temperature is controlled at 50-60°C, the dipping time is 5-10 minutes, and the glue coating amount is 25%-35%; S4, pre-curing: pre-curing in a hot air circulation oven at 90-110℃ for 15-25 minutes, with the volatile matter content ≤3%. After pre-curing, the residual bubbles are squeezed out by a roller press, and the pressure of the roller press is controlled between 2-4MPa; S5, lamination and segmented hot pressing: The first stage: temperature 120-130℃, pressure 5-8MPa, maintain pressure for 10-15 minutes to discharge gas; The second stage: heat up to 150-160℃, pressurize to 15-25MPa, maintain for 40-60 minutes; S6. Post-treatment: After gradient cooling at a cooling rate of ≤50°C / h, a phenolic cotton cloth laminate is obtained.
[0006] Furthermore, in step S1, the cotton cloth is replaced by a blended cloth of cotton fiber and polyester fiber with a blending ratio of 6:4, and the blended cloth is pretreated with a KH-570 silane coupling agent.
[0007] Furthermore, in step S2, 3wt%-8wt% of nano-alumina with a particle size of 50-150nm is added during the resin synthesis process, and dispersed by a three-roll mill to a particle size deviation of ≤5%.
[0008] Furthermore, in step S3, 0.1wt%-0.3wt% of an organosilicon defoamer is added to the thermoplastic phenolic resin, and the ultrasonic vibrator operates in an intermittent mode, wherein the intermittent mode operates for 5s and the interval is 10s.
[0009] Furthermore, in step S3, the dipping tank is connected to a vacuum system, and the vacuum degree of the vacuum system is set to between -0.05 MPa and -0.07 MPa, and the porosity of the substrate after dipping is ≤0.5%.
[0010] Furthermore, in step S4, the roller press uses a silicone roller surface, the roller speed is 0.5-1.5 m / min, and the bubble diameter on the surface of the substrate after rolling is ≤100 μm.
[0011] Furthermore, in step S5, 6n layers (n≥1) of pretreated cotton cloth are stacked, and a copper wire grid with a diameter of 0.1-0.3 mm and a spacing of 5-10 mm is laid between every 3-5 adjacent layers of cotton cloth. The copper wire grid is cross-arranged at an angle of 45°±5°, and is electroplated with nickel to form a 2-5 μm thick nickel coating before laying.
[0012] Furthermore, in step S5, during the staged hot pressing, the pressure fluctuation is monitored in real time by a piezoelectric pressure sensor. If the fluctuation amplitude is greater than 5%, the first stage pressure holding time is extended by 5-10 minutes.
[0013] Furthermore, step S6 also includes detecting the porosity of the substrate after impregnation by an industrial CT scanner at a resolution of 10 μm, and the detection area is not less than 5 random sampling points of 10 mm×10 mm. When the porosity of the substrate is greater than 0.5%, microgrooves with a depth of 20-50 μm are laser-etched on the surface of the phenolic cotton cloth laminate, and epoxy resin is injected into the existing pores to fill the defects.
[0014] Furthermore, the epoxy resin contains 1wt%-2wt% of silicon carbide powder with a particle size of 5-20 μm, and the surface hardness after curing is ≥2H.
[0015] A phenolic cotton cloth laminate prepared by the above method has the following characteristics: (a) Interlaminar shear strength ≥ 25MPa; (b) The bubble defect area accounts for ≤0.1%; (c) After 48h of heat and humidity cycling at 85℃ and 85%RH, the strength retention rate is ≥90%; (d) comprising phenolic resin layers with a thickness of 300-800 μm and modified cotton cloth layers with a thickness of 0.3-0.8 mm arranged alternately, wherein a mechanical interlocking structure with a depth of 5-15 μm is formed at the interface between the phenolic resin layer and the modified cotton cloth layer, which can be observed by a scanning electron microscope at a magnification of 5000.
[0016] Furthermore, the surface of the copper wires of the copper wire grid is coated with a nickel plating layer with a thickness of 2-5 μm, and the electromagnetic shielding effectiveness of the phenolic cotton cloth laminate is ≥25 dB at a frequency of 1 GHz.
[0017] Due to the adoption of the above technical solution, the beneficial effects achieved by the present invention are as follows: 1. As a preferred embodiment of the present invention, by adopting fiber pretreatment, ultrasonic vibrator and segmented hot pressing, the product performance and strength problems of phenolic cotton cloth laminate caused by bubble defects in the production process are effectively reduced. At the same time, it has a strong strength retention rate under wet and hot cycles, which is convenient for its application in wet and hot environments.
[0018] 2. As a preferred embodiment of the present invention, the control effect of bubbles is further improved by adding a defoaming agent, setting a vacuum environment in the dipping tank, and controlling the roller press, thereby effectively reducing the proportion of bubble defect area.
[0019] 3. As a preferred embodiment of the present invention, the porosity of the substrate after impregnation is detected by industrial CT. When the porosity of the substrate is greater than 0.5%, microgrooves are etched on the surface by laser, and epoxy resin is injected into the pores to fill the defects to remedy the bubbles. On the basis of enabling the laminate to achieve the expected performance and strength, its surface hardness is further improved, thereby achieving the purpose of reusing the defective substrate.
[0020] 4. As a preferred embodiment of the present invention, by laying a copper wire grid between cotton cloths, not only the performance parameters of the laminate are improved, but also the laminate has better electromagnetic shielding performance.
[0021] 5. As a preferred embodiment of the present invention, the cotton cloth layer substrate can be made of pure cotton cloth or a blended cloth of cotton fiber and polyester fiber. The use of blended cloth can form a mechanical interlocking structure at the interface between the phenolic resin layer and the blended cloth layer, thereby improving various performance parameters of the laminate. DETAILED DESCRIPTION
[0023] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.
[0024] In the description of this specification, the description with reference to the terms "implementation mode", "embodiment", "one embodiment", "example" or "specific example" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0025] Example 1 The preparation of phenolic cotton cloth laminate comprises the following steps: S1. Fiber pretreatment: After degreasing, the cotton cloth is treated in a nitrogen plasma device for 5 minutes at a power of 350-450W to form a microporous structure on the surface of the cotton cloth; S2, resin synthesis: phenol and formaldehyde are mixed in a molar ratio of 1:1.1-1.2, 0.8wt%-1.0wt% oxalic acid catalyst is added, and the mixture is reacted at 85-90°C for 2-2.5 hours to obtain a thermoplastic phenolic resin; S3, dipping and defoaming: dipping the cotton cloth treated in step S1 into the thermoplastic phenolic resin obtained in step S2, setting an ultrasonic vibrator in the dipping tank, the working frequency of the ultrasonic vibrator is 30-35kHz, the power density is 90-100W / m², the dipping temperature is controlled at 50-60°C, the dipping time is 8 minutes, and the glue coating amount is 25%-30%; S4, pre-curing: pre-curing in a hot air circulation oven at 100-110℃ for 20 minutes, with the volatile content ≤3%. After pre-curing, the residual bubbles are squeezed out by a roller press, and the pressure of the roller press is set to 3MPa; S5, lamination and segmented hot pressing: The first stage: temperature 120-130℃, pressure 5-8MPa, maintain pressure for 15 minutes and discharge gas; The second stage: heat up to 150-160℃, pressurize to 20-25MPa, maintain for 40-50 minutes; S6. Post-treatment: After gradient cooling at a cooling rate of ≤50°C / h, a phenolic cotton cloth laminate is obtained.
[0026] Example 2 The preparation of phenolic cotton cloth laminate comprises the following steps: S1. Fiber pretreatment: After pretreatment with KH-570 silane coupling agent, a blended fabric of cotton fiber and polyester fiber with a blending ratio of 6:4 was treated in a nitrogen plasma device for 8 minutes at a treatment power of 400-500W to form a microporous structure on the surface of the blended fabric; S2, resin synthesis: phenol and formaldehyde are mixed in a molar ratio of 1:1.2-1.3, 1.0wt%-1.5wt% oxalic acid catalyst is added, and the mixture is reacted at 90-95°C for 2-2.5 hours to obtain a thermoplastic phenolic resin; S3, dipping and defoaming: dipping the cotton cloth treated in step S1 into the thermoplastic phenolic resin obtained in step S2, setting an ultrasonic vibrator in the dipping tank, the working frequency of the ultrasonic vibrator is 25-30kHz, the power density is 80-90W / m², the dipping temperature is controlled at 50-60°C, the dipping time is 10 minutes, and the glue coating amount is 30%-35%; S4, pre-curing: pre-curing in a hot air circulation oven at 90-100℃ for 25 minutes, with the volatile matter content ≤3%. After pre-curing, the residual bubbles are squeezed out by a roller press, and the pressure of the roller press is set to 2MPa; S5, lamination and segmented hot pressing: The first stage: temperature 120-130℃, pressure 5-8MPa, maintain pressure for 10 minutes and discharge gas; The second stage: heating to 150-160℃, pressurizing to 15-20MPa, maintaining for 50-60 minutes; S6. Post-treatment: After gradient cooling at a cooling rate of ≤50°C / h, a phenolic cotton cloth laminate is obtained.
[0027] Example 3 The preparation of phenolic cotton cloth laminate comprises the following steps: S1. Fiber pretreatment: After degreasing, the cotton cloth is treated in a nitrogen plasma device for 3-5 minutes at a power of 300-400W to form a microporous structure on the surface of the cotton cloth; S2, resin synthesis: phenol and formaldehyde are mixed in a molar ratio of 1:1.0-1.1, 0.5wt%-0.8wt% of oxalic acid catalyst and 3wt%-8wt% of nano-alumina with a particle size of 50-150nm are added, and dispersed by a three-roll mill until the particle size deviation is ≤5%, and reacted at 90-95°C for 2-2.5 hours to obtain a thermoplastic phenolic resin; S3, dipping and defoaming: dipping the cotton cloth treated in step S1 into the thermoplastic phenolic resin obtained in step S2, setting an ultrasonic vibrator in the dipping tank, the working frequency of the ultrasonic vibrator is 30-35kHz, the power density is 110-120W / m², the dipping temperature is controlled at 50-60°C, the dipping time is 5-8 minutes, and the glue coating amount is 25%-30%; S4, pre-curing: pre-curing in a hot air circulation oven at 100-110℃ for 15-20 minutes, with the volatile content ≤3%. After pre-curing, the residual bubbles are squeezed out by a roller press, and the pressure of the roller press is set to 4MPa; S5, lamination and segmented hot pressing: The first stage: temperature 120-130℃, pressure 6-8MPa, maintain pressure for 12-15 minutes to discharge gas; The second stage: heat up to 150-160℃, pressurize to 15-20MPa, maintain for 40-50 minutes; S6. Post-treatment: After gradient cooling at a cooling rate of ≤50°C / h, a phenolic cotton cloth laminate is obtained.
[0028] Example 4 The phenolic cotton cloth laminate was prepared by the same steps as in Example 3, except that: In step S3, 0.1 wt% to 0.3 wt% of an organosilicon defoamer is added to the thermoplastic phenolic resin, and the ultrasonic vibrator operates in an intermittent mode, wherein the intermittent mode operates for 5 seconds and the interval is 10 seconds.
[0029] Example 5 The phenolic cotton cloth laminate was prepared by the same steps as in Example 3, except that: In step S3, the dipping tank is connected to a vacuum system, and the vacuum degree of the vacuum system is set between -0.05 MPa and -0.07 MPa. After dipping, the porosity of the substrate is ≤0.5%.
[0030] Example 6 The phenolic cotton cloth laminate was prepared by the same steps as in Example 3, except that: In step S4, the roller press uses a silicone roller surface, the roller speed is 0.5-1.5 m / min, and the bubble diameter on the surface of the substrate after rolling is ≤100 μm.
[0031] Example 7 The phenolic cotton cloth laminate was prepared by the same steps as in Example 3, except that: In step S5, 6 layers of pretreated cotton cloth are stacked, and a copper wire grid with a diameter of 0.1-0.3 mm and a spacing of 5-10 mm is laid between the third and fourth layers of cotton cloth. The copper wire grid is cross-arranged at an angle of 45°. The copper wire is electroplated with nickel before laying, and a 2-5 μm thick nickel plating layer is formed on the surface of the copper wire.
[0032] Example 8 The phenolic cotton cloth laminate was prepared by the same steps as in Example 3, except that: In step S5, during the segmented hot pressing, the pressure fluctuation is monitored in real time by a piezoelectric pressure sensor. During the detection process, it is found that the pressure fluctuation amplitude is greater than 5%. At this time, the first stage pressure holding time is extended by 5-10 minutes.
[0033] Example 9 The phenolic cotton cloth laminate was prepared by the same steps as in Example 3, except that: When performing step S6, the porosity of the substrate after impregnation is detected with a resolution of 10 μm by an industrial CT scanner, and no less than 5 random sampling points of 10 mm×10 mm are set in the detection area. When the porosity of the substrate is greater than 0.5%, microgrooves with a depth of 20-50 μm are laser-etched on the surface of the phenolic cotton cloth laminate, and epoxy resin is injected into the existing pores to fill the defects.
[0034] Example 10 The phenolic cotton cloth laminate was prepared by the same steps as in Example 9, except that: The epoxy resin contains 1wt%-2wt% of silicon carbide powder with a particle size of 5-20μm, and the surface hardness after curing is ≥2H.
[0035] Comparative Example 1 The phenolic cotton cloth laminate was prepared by the same steps as in Example 1, except that: In step S3, no ultrasonic vibrator is provided in the dipping tank.
[0036] Comparative Example 2 The phenolic cotton cloth laminate was prepared by the same steps as in Example 1, except that: In step S5, after lamination, no segmented hot pressing is performed, and hot pressing is performed directly for 40-50 minutes at a temperature between 150-160° C. and a pressure between 20-25 MPa.
[0037] Comparative Example 3 The phenolic cotton cloth laminate was prepared by the same steps as in Example 8, except that: In step S5, during the segmented hot pressing, the pressure fluctuation is monitored in real time by a piezoelectric pressure sensor. During the detection process, it is found that the pressure fluctuation amplitude is greater than 5%. At this time, no measures are taken to extend the pressure holding.
[0038] Comparative Example 4 The phenolic cotton cloth laminate was prepared by the same steps as in Example 9, except that: When performing step S6, the porosity of the substrate after impregnation is detected with a resolution of 10 μm by an industrial CT scanner, and no less than 5 random sampling points of 10 mm×10 mm are set in the detection area. When the porosity of the substrate is greater than 0.5%, no defect filling measures are taken.
[0039] Table 1 shows the test results of interlaminar shear strength, bubble defect area ratio and wet heat strength retention rate of Examples 1-10 and Comparative Examples 1-4.
[0040] The interlaminar shear strength is tested according to the standard test method of GB / T30969-2014; the area percentage of bubble defects is measured by ultrasonic C-scanning, using a high-frequency probe (5~20MHz) with a resolution of 50~200μm. After generating a C-scan image, the bubble area is marked by software (such as UltraPAC) to calculate the area percentage; the wet heat strength retention rate is tested in accordance with relevant standards such as GB / T2423.3-2006 and GB / T1458-2008.
[0041] Each test result is the average value of 10 test results of the same batch of samples obtained in the same embodiment or comparative example after removing the maximum and minimum values.
[0042] Table 1 Test results of interlaminar shear strength, bubble defect area ratio and wet heat strength retention rate of Examples 1-10 and Comparative Examples 1-4
[0043] Through Table 1, it can be seen from Example 1 and Example 2 that after the cotton cloth layer substrate is made of pure cotton cloth or cotton fiber and polyester fiber blended cloth, the interlaminar shear strength and moisture heat retention rate of the laminate are significantly improved due to the mechanical interlocking structure formed by the blended cloth at the interface between the phenolic resin layer and the blended cloth layer. It can be seen from Example 1 and Example 3 that after adding nano-alumina dispersion in the phenolic resin, the interlaminar shear strength and moisture heat retention rate of the laminate are also significantly improved. It can be seen from Example 3 and Example 4, Example 5, and Example 6 that after adding defoamer, connecting the vacuum system and controlling the rolling speed of the roller press, the proportion of bubble defects in the laminate is also significantly reduced. It can be seen from Example 3 and Example 7 that after the copper grid is placed, the interlaminar shear strength and moisture heat retention rate of the laminate are significantly improved, greatly increasing its strength. By comparing Example 3, Example 8 and Comparative Example 3, it can be seen that when pressure fluctuations occur, if the holding time is extended, the interlaminar shear strength and moisture retention rate of the laminate will be slightly improved, and the proportion of bubble defects will also be slightly reduced. If measures are not taken to extend the holding time, the interlaminar shear strength and moisture retention rate of the laminate will be greatly reduced, and the proportion of bubble defects will also be greatly increased. It can be seen that extending the holding time can not only eliminate the defects in the early stage, but also slightly improve its performance. By comparing Example 3, Example 9, Example 10 and Comparative Example 4, it can be seen that when the proportion of bubble defects is large, by laser etching microgrooves on the surface of the phenolic cotton cloth laminate, injecting epoxy resin into the existing pores to fill the defects, not only can the influence of bubbles on product performance and strength be eliminated, but also the interlaminar shear strength and moisture retention rate of the laminate can be slightly improved after epoxy resin filling. It can be seen from Example 1 and Comparative Example 1 and Example 1 and Comparative Example 2 that the use of ultrasonic vibrators and segmented lamination can effectively reduce the proportion of bubble defects and improve the performance and strength of the laminate.
[0044] Table 2 shows the test results of the electromagnetic shielding effectiveness of multiple samples in Example 3 and Example 7. The electromagnetic shielding effectiveness was tested in accordance with GB / T 30142 standard using a frequency of 1 GHz.
[0045] Table 2 Electromagnetic shielding effectiveness test results
[0046] By comparing Example 1 and Example 3, it can be seen that after adding nano-alumina, the electromagnetic shielding effectiveness of the laminate is greatly improved. By comparing Example 3 and Example 7, it can be seen that after adding copper grid, its electromagnetic shielding effectiveness is further improved.
[0047] Anything not described in the present invention can be achieved by adopting or drawing on existing technologies.
[0048] The various embodiments in this specification are described in a progressive manner, and the same or similar parts between the various embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.
[0049] The above description is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of the claims of the present invention.
Claims
1. A preparation process of a phenolic cotton cloth laminate, characterized in that: The following steps are involved: S1. Fiber pretreatment: After degreasing, the cotton cloth is treated in a nitrogen plasma device for 3-8 minutes at a power of 300-500W to form a microporous structure on the surface of the cotton cloth; S2, resin synthesis: phenol and formaldehyde are mixed in a molar ratio of 1:1.0-1.3, 0.5wt%-1.5wt% oxalic acid catalyst is added, and the mixture is reacted at 85-95°C for 2-2.5 hours to obtain a thermoplastic phenolic resin; S3, dipping and defoaming: dipping the cotton cloth treated in step S1 into the thermoplastic phenolic resin obtained in step S2, setting an ultrasonic vibrator in the dipping tank, the working frequency of the ultrasonic vibrator is 25-35kHz, the power density is 80-120W / m², the dipping temperature is controlled at 50-60°C, the dipping time is 5-10 minutes, and the glue coating amount is 25%-35%; S4, pre-curing: pre-curing in a hot air circulation oven at 90-110℃ for 15-25 minutes, with the volatile matter content ≤3%. After pre-curing, the residual bubbles are squeezed out by a roller press, and the pressure of the roller press is controlled between 2-4MPa; S5, lamination and segmented hot pressing: The first stage: temperature 120-130℃, pressure 5-8MPa, maintain pressure for 10-15 minutes to discharge gas; The second stage: heating to 150-160℃, pressurizing to 15-25MPa, maintaining for 40-60 minutes; S6. Post-treatment: After gradient cooling at a cooling rate of ≤50°C / h, a phenolic cotton cloth laminate is obtained.
2. The preparation process of the phenolic cotton cloth laminate according to claim 1, characterized in that: In step S1, the cotton cloth is replaced by a blended cloth of cotton fiber and polyester fiber with a blending ratio of 6:4, and the blended cloth is pretreated with a KH-570 silane coupling agent.
3. The preparation process of the phenolic cotton cloth laminate according to claim 1, characterized in that: In step S2, 3wt%-8wt% of nano-alumina with a particle size of 50-150nm is added during the resin synthesis process, and dispersed by a three-roll mill to a particle size deviation of ≤5%.
4. The preparation process of the phenolic cotton cloth laminate according to claim 1, characterized in that: In step S3, 0.1 wt% to 0.3 wt% of an organosilicon defoamer is added to the thermoplastic phenolic resin, and the ultrasonic vibrator operates in an intermittent mode, wherein the intermittent mode operates for 5 seconds and the interval is 10 seconds.
5. The preparation process of the phenolic cotton cloth laminate according to claim 1 or 4, characterized in that: In step S3, the dipping tank is connected to a vacuum system, and the vacuum degree of the vacuum system is set to between -0.05 MPa and -0.07 MPa. After dipping, the porosity of the substrate is ≤0.5%.
6. The preparation process of the phenolic cotton cloth laminate according to claim 1, characterized in that: In step S4, the roller press uses a silicone roller surface, the roller speed is 0.5-1.5 m / min, and the bubble diameter on the surface of the substrate after rolling is ≤100 μm.
7. The preparation process of the phenolic cotton cloth laminate according to claim 1, characterized in that: In step S5, 6n layers (n≥1) of pretreated cotton cloth are stacked, and a copper wire grid with a diameter of 0.1-0.3 mm and a spacing of 5-10 mm is laid between every 3-5 adjacent layers of cotton cloth. The copper wire grid is cross-arranged at an angle of 45°±5°, and is electroplated with nickel before laying to form a nickel plating layer with a thickness of 2-5 μm.
8. The process for preparing the phenolic cotton cloth laminate according to claim 1, characterized in that: Step S6 also includes detecting the porosity of the substrate after impregnation with an industrial CT scanner at a resolution of 10 μm, and the detection area is not less than 5 random sampling points of 10 mm×10 mm. When the porosity of the substrate is greater than 0.5%, microgrooves with a depth of 20-50 μm are laser-etched on the surface of the phenolic cotton cloth laminate, and epoxy resin is injected into the existing pores to fill the defects.
9. A phenolic cotton cloth laminate, prepared by the method according to any one of claims 1 to 8, characterized in that: (a) Interlaminar shear strength ≥ 25MPa; (b) The bubble defect area accounts for ≤0.1%; (c) After 48h of heat and humidity cycling at 85℃ and 85%RH, the strength retention rate is ≥90%.
10. The phenolic cotton cloth laminate according to claim 9, characterized in that: The copper wire surfaces of the copper wire grid are coated with a nickel plating layer with a thickness of 2-5 μm, and the electromagnetic shielding effectiveness of the phenolic cotton cloth laminate is ≥25 dB at a frequency of 1 GHz.
Citation Information
Patent Citations
Structural flame-retardant functional composite material and preparation method thereof
CN112009038A
Electrical grade laminates
GB1204519A
Phenolic laminating resins
GB1278582A
Method of manufacturing composite laminates
IN139241B
Manufacture of laminated plate
JP1981015320A